Estudo microfaciológico e quimioestratigráfico de calcários do Grupo Macaé a partir de uma seção distal da Bacia de Campos - Caetano Filho, Sergio [UNESP] (2015)
Late Aptian-Early Albian marine limestones from the basins of eastern Brazilian Continental Margin record the early stages of the South Atlantic Ocean (SA). Fossil assemblages and geochemical signatures of these rocks indicate marine incursions from Tethys paleocean in this restricted sea, with organic-rich sediments and planktic foraminiferal bioevents registered. The Late Aptian-Early Albian transition is marked by paleoclimatic and paleoceanographic changes which resulted in global carbon cycle perturbations. The investigation of this interval at the SA and its stratigraphic correlation with coeval sections promote a better understanding and temporal definition of the geological processes that occurred in this setting, which are fundamental to petroleum exploration. This work presents the chemostratigraphy and microfacies analysis of a distal section of the Macaé Group (Late Aptian-Cenomanian), in Campos Basin, focusing on the paleoenvironmental characterization and global correlations to the base of this unit. The study of microfacies was carried out by petrography, cathodoluminescence and SEM/EDS analysis. The chemostratigraphy encompassed C, O and Sr isotopes, major, minor and trace elements, TOC and pyrolysis analysis. The results allowed the section division into six informal units, I to IV (bottom to the top), and its association with Quissamã and Outeiro formations, which record a gradual platform drowning and more humid climate conditions. Six microfacies were identified in units I and III, which were grouped in five microfaciological associations in a carbonate ramp model. In unit I, the microfacies are composed by benthic-dominated wackestones and packstones (CCB and C*CB) deposited on the inner-ramp/inter-bank and its flanks (AM-1 and AM-2, respectively), in a proximal and oxygenated environment. The microfacies from unit III (CPP, C*PP and C*RP) are composed by planktic-dominated mudstones and wackestones, deposited on the...